The European educational space and the construction of European identity - Toksöz, Fügen (My University, 2008)
The European integration project founded with the aim of providing a lasting peace in the Continent in 1957 has developed from an economic community of six into a union of twenty-seven member states. Today, the European Union is no more a simple free trade area or only an intergovernmental structure with limited objectives on economic issues. It has moved far beyond an international organization and evolved into a unified and unique entity over the fifty-one years that have passed since its first establishment. From a modest economic community, it has evolved into a political entity which functions by means of both intergovernmental and supranational methods. However, the unsolved unemployment problem, which started with the economic crisis in the 70s and continued with the challenges of globalization, caused European people to be discontented with their situation. Furthermore, the steps taken for political integration has brought forth the legitimacy problem, which stems from the democratic deficit of the Union, requires the construction of a well-informed cohesive body of citizens, namely, a ‘demos’. The emergence of this need has increased the necessity for the construction of European identity. As a solution to these two crucially important issues, after the Maastricht Treaty the Union gave momentum to the developments in the field of education by expanding the cooperation between the member states and by creating a new educational space. The European Area of Higher Education, which was launched with the Bologna Declaration and continued to develop with the Bologna process, has been the most ambitious step taken in the field of education so far. Parallel to its objective of constructing a coherent and compatible European area of higher education with a view to reform and converge the existing structures while preserving the autonomy of higher education institutions and respecting national, cultural and linguistic differences, the European Area of Higher Education has improved the competency and the competitiveness of Europe and the Europeans in the global market. Furthermore, the mobility, the multicultural and multilingual spaces that it provides for the people of Europe promotes a civic dimension and a sense of belonging to Europe which is an important dimension in the construction of European identity. Within this framework, this study explicates and exhibits the role and the impact of education and the European educational space on the construction of European identity and the development of Union citizenship from a social constructivist perspective. In order to reach a comprehensive assessment, the creation of the European educational space with its key actors and documents are examined in a historical perspective, discourse analyses of the two pivotal educational documents; the 1995 White Paper and the Bologna Declaration are made, and the concept of identity, its construction process and the role of education in this process is explored in detail. As a result of these meticulous explorations, it is concluded that the creation of the European Area of Higher Education as a part of the European educational space could play a major role in the construction of European identity and the development of Union citizenship which could be a solution for the legitimacy problem of the European Union.

1957’de Avrupa’da uzun süreli barışı sağlamak için başlatılan Avrupa bütünleşme projesi sadece altı üye devletten oluşan ekonomik bir topluluktan yirmi yedi üyesi olan bir birliğe dönüşmüştür. Aradan geçen 51 yıllık süre içinde Avrupa Birliği sadece bir serbest ticaret bölgesi ya da amaçları sadece ekonomik konularla sınırlı uluslararası yapıya sahip bir oluşum olmanın çok ötesinde hem uluslararası hem de uluslarüstü yöntemlerle işleyen kendine özgü siyasi bir birlik halini almıştır. Ancak bugün, 70lerde başlayan ve küreselleşmenin getirdiği zorluklarla günümüze kadar devam eden ve hala çözümlenemeyen işsizlik problemi Avrupalıları kaygılandırmaktadır. Ayrıca siyasi bütünleşme için atılan adımlar demokrasi eksikliğinden kaynaklanan meşruiyet tartışmalarını da beraberinde getirmiştir. Birliğin demokrasi eksiğini giderebilmesi için demos’a, başka bir deyişle, ortak değerler üzerinde birleşmiş bir topluma ihtiyacı vardır. Bu ihtiyaç da ortak bir Avrupa kimliğinin yapılandırılması gereğini ortaya çıkarmıştır. Avrupa Birliği, eğitimi bu iki önemli soruna çözüm olarak görmüş ve özellikle Maastricht Antlaşması sonrası üye devletlerin eğitim alanındaki işbirliğini hızlandırıp genişleterek Avrupa eğitim alanının yapılandırılmasını sağlamıştır. Bolonya Deklarasyonuyla temelleri atılan ve Bolonya süreciyle oluşumu devam eden Avrupa Yüksek Öğretim Alanı şu ana kadar bu yönde atılan en önemli adım olmuştur. Bu oluşumun temel amaçlarından biri ulusal, kültürel ve dilsel farklılıkları ve yüksek öğretim kurumlarının özerkliğini koruyarak, bu kurumların hali hazırda varolan eğitim yapılarını iyileştirerek ve birbirine yakınlaştırarak kaliteli ve bütünleşmiş bir Avrupa eğitim alanı yaratmaktır. Diğer bir amacı ise Avrupa’nın ve Avrupalıların küresel pazardaki rekabet gücünü arttırarak işsizlik sorununa çözüm bulmaktır. Ayrıca, bu alanın sağladığı hareketlilik, çok-kültürlü ve çok-dilli sosyal alanlar Avrupa bilincinin ve kimliğinin oluşturulması için gerekli ‘sivik’ boyutu oluşturmaktır. Bu çerçeve içinde, eldeki çalışma Avrupa eğitim alanının, Avrupa kimliğinin oluşturulması ve Avrupa Birliği vatandaşlığının geliştirilmesi üzerindeki rolünü ve etkilerini sosyal inşacı açıdan incelemekte ve göstermektir. Kapsamlı bir sonuca varabilmek için Avrupa eğitim alanı temel oyuncuları ve belgeleriyle tarihi bir perspektif içinde incelenmiş, en önemli eğitim belgelerinden olan 1995 Beyaz Kitabı ve Bolonya Deklarasyonunun söylem analizi yapılmış, ve kimlik kavramı, gelişim süreci ve bu süreçte eğitimin rolü araştırılmıştır. Tüm bu detaylı ve titiz çalışmaların sonucunda, Avrupa eğitim alanının bir parçası olarak oluşturulan Avrupa Yüksek Öğretim Alanının Avrupa kimliği ve Avrupa Birliği vatandaşlığının inşasında önemi yadsınamaz bir rol oynayacağı ve bunun da Avrupa Birliğinin meşruiyet sorununa çözüm getirebileceği sonucuna varılmıştır.
Keywords: Eğitim_Avrupa Biriliği; Kültürel Kimlik